The Impact of Influencer Credibility on Consumer Purchasing Decisions: A Case Study on the Fashion Industry in Indonesia - Desma Erica Maryati M; Eva Yuniarti Utami; Roosganda Elizabeth (West Science Interdisciplinary Studies, 2023)
Indonesia's fashion sector has grown dramatically in recent years, driven primarily by influencer marketing's ascent to prominence in advertising and consumer interaction. Within this dynamic framework, influencer credibility—which includes competence, trustworthiness, and attractiveness—has emerged as a critical component in influencing consumer purchasing decisions. This study uses a mixed-methods approach to examine the complex relationship between customer behavior and influencer credibility in the Indonesian fashion business. It combines quantitative surveys with qualitative interviews. Our research suggests that dependability and competence are important aspects of influencer credibility that favorably affect consumers' decisions to buy. Although relevant, attractiveness has a relatively smaller impact. Furthermore, it was found that cultural relevance was a significant element, as consumers favored influencers that shared the norms and values of Indonesian culture. These insights offer a deeper knowledge of the interaction between influencers and customers in Indonesia's dynamic fashion market, which is helpful advice for influencers and marketers alike as they try to optimize their tactics in this quickly changing scene.